The PRIDE database resources in 2022: a hub for mass spectrometry-based proteomics evidences. Issue Volume 50:Issue D1(2022) (1st November 2021) - Perez-Riverol, Yasset; Bai, Jingwen; Bandla, Chakradhar; García-Seisdedos, David; Hewapathirana, Suresh; Kamatchinathan, Selvakumar; Kundu, Deepti J; Prakash, Ananth; Frericks-Zipper, Anika; Eisenacher, Martin; Walzer, Mathias; Wang, Shengbo; et al.
Abstract: The PRoteomics IDEntifications (PRIDE) database (https://www.ebi.ac.uk/pride/ ) is the world's largest data repository of mass spectrometry-based proteomics data. PRIDE is one of the founding members of the global ProteomeXchange (PX) consortium and an ELIXIR core data resource. In this manuscript, we summarize the developments in PRIDE resources and related tools since the previous update manuscript was published in Nucleic Acids Research in 2019. The number of submitted datasets to PRIDE Archive (the archival component of PRIDE) has reached on average around 500 datasets per month during 2021. In addition to continuous improvements in PRIDE Archive data pipelines and infrastructure, the PRIDE Spectra Archive has been developed to provide direct access to the submitted mass spectra using Universal Spectrum Identifiers. As a key point, the file format MAGE-TAB for proteomics has been developed to enable the improvement of sample metadata annotation. Additionally, the resource PRIDE Peptidome provides access to aggregated peptide/protein evidences across PRIDE Archive. Furthermore, we will describe how PRIDE has increased its efforts to reuse and disseminate high-quality proteomics data into other added-value resources such as UniProt, Ensembl and Expression Atlas.